Exploração de fatores relacionados a processos de aprendizagem autorregulada em contexto de desenvolvimento profissional - Piazentini, Luiz Henrique (2022)
This exploratory research aims to investigate the learner’s experience when defining a scope to learn a new competence, and how professional adults working in startup or small companies can be digitally supported in the process of independent upskilling. Over the last three decades, the set of competences expected from these employees has followed many changes and technical developments, consequence of digital technologies development. Whilst some theorists and specialists have been investigating Self-Regulated Learning (SRL) in online educational contexts, the mechanisms influencing SRL in online professional development contexts have not yet been fully understood. With that in mind, this thesis project’s hypothesis is that in the professional development contexts, the scope of what adult professionals decide to learn should also be considered as part of SRL models. Through research, selection, validation and application of most recent SRL models, this work will base its studies on Winne and Hadwin’s (1998) theoretical framework, which currently involves 4 phases: task definition, goals and planning, applying strategies, and reflection and adaptation. Furthermore, with studies based on the aforementioned theoretical framework, this thesis proposes a new phase in the SRL process, taking into account “scope definition”. The proposed model is the result of reviews on empirically tested SRL models, and on frameworks of 21st century competences as outlined by OECD, UNESCO and WEF. The proposition of the new phase added to SRL models based on Winne and Hadwin’s (1998), was carried out through an experiment with 18 employees from an startup company in Brazil, invited to interact with the SRL prototype over a 12-weeks period. In order to analyse the data generated by the SRL application, a qualitative approach was adopted, alongside thematic analysis, to understand forms of interaction with the prototype and possible co-designed interventions with participants. This approach is compared with existing SRL models’ in-depth review to understand how scope setting supports selfregulation of learning. The results showed that in addition to the sub-constructs presented that made up the new scoping phase – feedback, interests and 21st century competences – a new sub-construct emerged, associated with the feedbacks: the cognitive equilibration, composed of the elements assimilation and accommodation derived from Piaget’s (1978) theories